2016
DOI: 10.1016/j.neuroimage.2016.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neural patterns of social cognition for cooperation versus competition

Abstract: How do people consider other minds during cooperation versus competition? Some accounts predict that theory of mind (ToM) is recruited more for cooperation versus competition or competition versus cooperation, whereas other accounts predict similar recruitment across these two contexts. The present fMRI study examined activity in brain regions for ToM (bilateral temporoparietal junction, precuneus, dorsomedial prefrontal cortex) across cooperative and competitive interactions with the same individual within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 87 publications
2
30
0
Order By: Relevance
“…While condition differences appear between ages 3 and 4 for Study 1 and at age 4 for Study 2 (possibly reflecting greater task difficulty for Study 2 as compared to Study 1), no condition difference emerges at age 5 in either study. These results suggest that any specific ToM advantage for competition may emerge when ToM first comes online but then may diminish over time, at least in the context of the present tasks-a suggestion that converges with our prior work showing that brain regions implicated in ToM are recruited to a similar extent for cooperation and competition in adults but these regions nevertheless encode differences relevant to ToM between the two contexts (Tsoi et al, 2016). However, the extent to which this diminished advantage can be attributed to schooling and greater exposure to perspective-taking in cooperative contexts (e.g., sharing with others in school settings) is unclear.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While condition differences appear between ages 3 and 4 for Study 1 and at age 4 for Study 2 (possibly reflecting greater task difficulty for Study 2 as compared to Study 1), no condition difference emerges at age 5 in either study. These results suggest that any specific ToM advantage for competition may emerge when ToM first comes online but then may diminish over time, at least in the context of the present tasks-a suggestion that converges with our prior work showing that brain regions implicated in ToM are recruited to a similar extent for cooperation and competition in adults but these regions nevertheless encode differences relevant to ToM between the two contexts (Tsoi et al, 2016). However, the extent to which this diminished advantage can be attributed to schooling and greater exposure to perspective-taking in cooperative contexts (e.g., sharing with others in school settings) is unclear.…”
Section: Discussionsupporting
confidence: 89%
“…We previously investigated the question of whether ToM is greater for competition vs. cooperation or vice versa in adults, using overall levels of activity in brain regions implicated in ToM as a proxy for the cognitive process of ToM (Tsoi, Dungan, Waytz, & Young, 2016). We found that while overall levels of activity within ToM regions were similar for cooperative and competitive interactions, these regions nevertheless encoded information separating cooperation from competition in their spatial patterns of activity.…”
Section: Introductionmentioning
confidence: 98%
“…playing a computer game against an unseen opponent) typically recruit fronto-parietal regions (e.g. superior frontal gyrus and superior parietal gyrus; Decety et al, 2004 ) that may include mentalizing network regions such as TPJ and precuneus ( Tsoi et al, 2016 ) but no pSTS responses are noted. Further research should aim to clarify the extent to which visual interactive cues are modulated by viewer perspective, along with the contribution of social cognition to responses in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…Classification accuracies around this level may reflect difficulty with classification of more abstract features; indeed, classification accuracies are similar across many studies examining socially relevant, higher level features (e.g. Chiu et al , 2011 ; Kaul et al , 2011 ; Ratner et al , 2013 ; Anzellotti et al , 2014 ; Tsoi, Dungan, Waytz, & Young, 2016 ). As more researchers start using MVPA to address socially- and morally relevant questions, we may be able to better characterize specific features that lead to lower classification accuracies.…”
Section: Limitationsmentioning
confidence: 79%